Dendrite‐Free Lithium Deposition via a Superfilling Mechanism for High‐Performance Li‐Metal Batteries. Issue 41 (29th August 2019) - Wang, Qian; Yang, Chengkai; Yang, Jijin; Wu, Kai; Hu, Cejun; Lu, Jing; Liu, Wen; Sun, Xiaoming; Qiu, Jingyi; Zhou, Henghui
Abstract: Uncontrollable Li dendrite growth and low Coulombic efficiency severely hinder the application of lithium metal batteries. Although a lot of approaches have been developed to control Li deposition, most of them are based on inhibiting lithium deposition on protrusions, which can suppress Li dendrite growth at low current density, but is inefficient for practical battery applications, with high current density and large area capacity. Here, a novel leveling mechanism based on accelerating Li growth in concave fashion is proposed, which enables uniform and dendrite‐free Li plating by simply adding thiourea into the electrolyte. The small thiourea molecules can be absorbed on the Li metal surface and promote Li growth with a superfilling effect. With 0.02 m thiourea added in the electrolyte, Li | Li symmetrical cells can be cycled over 1000 cycles at 5.0 mA cm −2, and a full cell with LiFePO4 | Li configuration can even maintain 90% capacity after 650 cycles at 5.0 C. The superfilling effect is also verified by computational chemistry and numerical simulation, and can be expanded to a series of small chemicals using as electrolyte additives. It offers a new avenue to dendrite‐free lithium deposition and may also be expanded to other battery chemistries. Abstract : The thiourea molecule is used to direct Li growth in a concave fashion, rather than convex, through a superfilling mechanism. This enables dendrite‐free Li growth with a smooth surface, even after 1000 cycles. Moreover, dendrites can be self‐healing and surface cracks can be repaired effectively by this mechanism, which means a short‐circuited cell can run well again after the addition of thiourea.